2014
DOI: 10.3109/0886022x.2014.882238
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of recurrent focal segmental glomerulosclerosis with a low dose rituximab in a kidney transplant recipient

Abstract: Recurrence of focal segmental glomerulosclerosis (FSGS) is a major therapeutic challenge in kidney transplantation (KT). Although intensive plasmapheresis and high-dose rituximab have been introduced to treat recurrent FSGS, the most effective dosage and regimen of rituximab have not been determined. Herein we reported the first case of successful treatment of recurrent FSGS with a low-dose rituximab. The patient showed marked proteinuria (3.5 g/d) and oliguria 2 d after KT. Two courses of plasmapheresis and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 22 publications
0
16
0
1
Order By: Relevance
“…Cho et al [80] Rituximab ® (100 mg, 1 dose) 1 patient (≥ 18 yr) Complete remission Yabu et al [87] [104] Abatacept (1 dose; 10 mg/kg) in patient 1; belatacept (3 doses 10 mg/kg or continuative treatment) in patients 2-5…”
Section: Messina M Et Al Focal Segmental Glomerulosclerosis In Renamentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al [80] Rituximab ® (100 mg, 1 dose) 1 patient (≥ 18 yr) Complete remission Yabu et al [87] [104] Abatacept (1 dose; 10 mg/kg) in patient 1; belatacept (3 doses 10 mg/kg or continuative treatment) in patients 2-5…”
Section: Messina M Et Al Focal Segmental Glomerulosclerosis In Renamentioning
confidence: 99%
“…Despite successful results having been obtained [77][78][79][80][81][82][83][84][85][86] , other studies have shown a transient or even absent response to Rituximab ® [62,[87][88][89][90][91][92][93][94] (Table 1).…”
Section: Novel Therapeutic Optionsmentioning
confidence: 99%
“…However, the question of rituximab dosing should be considered open, especially in view of a recent case report documenting effective treatment of recurrent FSGS with a single 100-mg dose of the antibody [80]. An additional concern with the use of rituximab is the side-effect profile.…”
Section: Treatmentmentioning
confidence: 99%
“…Recently, small studies have shown that a single rituximab dose was efficacious for treatment of primary/relapsing IgA, FSGS, MN, MPGN, or minimal change disease [24,25,26]. Pharmacokinetic studies have illustrated that lower doses of rituximab are effective in prompt and sustained depletion of B-cells up to 12 months, with count recovery beginning between 3 and 6 months [25,26,27].…”
Section: Introductionmentioning
confidence: 99%